Literasi informasi pada proses pembelajaran jarak jauh di TK Islam Arafah di Jakarta - Rizky Nofit Maulana; Rohanda Rohanda; Fitri Perdana (Faculty of Communication, Padjadjaran University, 2022)
This research discusses about literacy distance learning at Arafah Islamic Kindergarten Jakarta based on lesson plans; learning methods; learning activities; and post-learning activities. This study aims to describe information literacy through distance learning activities at Arafah Islamic Kindergarten in Jakarta. The method used in this research is a qualitative method with a case study approach. Data is collected through observation, interviews, documentation, and literature studies. The researcher selected informants with purposive sampling method which sellect the principal, teachers, and parents of students of Arafah Islamic Kindergarten Jakarta. The results of this study explain that distance learning or online learning began to emerge during the Covid-19 pandemic as suggested by the Ministry of Education and Culture, including in terms of learning literacy in children. Arafah Islamic Kindergarten Jakarta itself has created a special curriculum for distance learning activities based on philosophical, sociological, and psycho-pedagogical aspects. At Arafah Islamic Kindergarten Jakarta, literacy learning and basic numeracy literacy are taught remotely using the resource-based learning method and scientific approach. The school has tried to teach children literacy effectively and efficiently by innovating learning activities through children's worksheets, home-visit activities, and video learning. After the learning activities, the school provides assessments through weekly report cards. To optimize distance learning activities, the school collaborates with parents or guardians in every distance learning activity.